The Influence of Judicial Decisions on the Legal Position of the Consumer in the Market for Electricity and Gas - Czarnecka, Marzena (Studia Oeconomica Posnaniensia, 2015)
Agreements concluded with individual customers receiving electricity or gas from energy suppliers are contracts regulated by a separate Energy Law. Modern methods of liberalization and the regulation of gas and energy are aimed at the empowerment of the consumer. Polish Energy Law affects the functioning of the energy and gas markets by ensuring the availability of electricity and gas for the widest range of people, at a fixed price. However, the introduction of any kind of regulation in the form of statutory controls means the state limiting economic activity; therefore, it is important that the case law shapes the legal framework and the functioning of the consumer market. As regards the two issues presented in the paper, that is the form of the contract and suspending the provision of energy and gas, this is indeed the situation. In the opinion of the author it is case law that has shaped the behaviour of firms and consumers in this area.